The Battle of Saipan in Japanese Civilian Memoirs: Non-combatants, Soldiers and the Complexities of Surrender. Issue 3 (3rd July 2018) - Trefalt, Beatrice
ABSTRACT: In Japan, 'Saipan' refers both to a nearby tropical holiday, and to the site of a battle that annihilated Japanese troops, embroiled the large population of Japanese residents on the island and ultimately spelled the end of the Japanese empire, now within the reach of bombers. In other places, and particularly amongst the Allies, Saipan conjures up images of civilians jumping to their death rather than facing capture, leading to simplistic assessments about fanaticism being rife across all sections of Japanese society; to a focus on suicide that overshadows the true extent of the battle's collateral damage; and to largely unexamined statements about military exploitation of civilians and the murder of civilians in extremis. This article uses the memoirs of civilian survivors of the battle to reflect on the civilian experience of the battle of Saipan, relationships between Japanese combatants and non-combatants during the fighting, and the complexities of surrender.